2010
DOI: 10.1111/j.1600-0838.2008.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercising impressive impressions: the exercise stereotype in male targets

Abstract: The main purpose of this study was to investigate the exercise stereotype and the non-exerciser stereotype on male targets, and the moderating effects of impression motivation in 184 female and 73 male Swedish undergraduate students. The participants read a description of one of the following male targets: a typical exerciser, an active living target, an excessive exerciser, a non-exerciser, or a control target, and then rated these targets on 12 personality (e.g. lazy-hard worker, dependent-independent) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
3
11
1
Order By: Relevance
“…Whatever the health status of the targets, we observed that being an exerciser elicited higher perceived competence and warmth compared with the non‐exercising targets and the control targets. These findings are consistent with previous research on the exerciser stereotype (e.g., Martin et al., ; Martin Ginis & Leary, ; Lindwall & Ginis, ). For instance, Martin et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whatever the health status of the targets, we observed that being an exerciser elicited higher perceived competence and warmth compared with the non‐exercising targets and the control targets. These findings are consistent with previous research on the exerciser stereotype (e.g., Martin et al., ; Martin Ginis & Leary, ; Lindwall & Ginis, ). For instance, Martin et al.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the meaningfulness of the results, the effect sizes concerning the competence dimension were comparable with those of previous studies on the exerciser stereotype (e.g., Lindwall & Ginis, ). But overall, the effect sizes were quite modest.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, in athletic populations, the importance of lower intensity–high-volume training should not be overlooked. Laursen (2010) in a critical review of low and high volume and intensity training suggested that training for sports performance should have an appropriate blend of both HIT and high-volume training, otherwise performance ability can stagnate. A polarized approach for optimal intensity distribution for the training of elite athletes of intense events (rowing, swimming, track running, and cycling) was suggested by Laursen (2010), whereby 75% of total training volume should be performed at low intensities, and 10–15% should be performed at very high intensities.…”
Section: High-intensity Training: a Powerful And Time-efficient Exercmentioning
confidence: 99%
“…At the same time, the “energy crisis” that results in decreased ATP and increased adenosine mono phosphate (AMP) activates the AMP-activated protein kinase (Gibala, 2009; Laursen, 2010). Activation of p38 mitogen-activated protein kinase (MAPK), possibly via increase generation of ROS may also be involved (Gibala et al, 2012).…”
Section: High-intensity Training: a Powerful And Time-efficient Exercmentioning
confidence: 99%